2023
DOI: 10.3390/microorganisms11020509
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Effect of Unifloral Honeys against Bacteria Isolated from Chronic Wound Infections

Abstract: Honey is known as an alternative remedy for the treatment of wounds. To evaluate the potential of five Hungarian honey types against wound-associated bacteria, in vitro microbiological assays were conducted on Pseudomonas aeruginosa, Staphylococcus epidermidis and methicillin-resistant Staphylococcus aureus (MRSA). Minimum inhibitory concentration (MIC) was determined with the broth macrodilution method, and biofilm degradation capacity was tested with a crystal violet assay. To understand the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Among unifloral honeys, which are derived predominantly from a certain plant species or genus, the amber to dark brown, somewhat bitter-tasting chestnut honey proved to be superior in terms of antibacterial activity in comparison to other honey types from Portugal [ 16 ], Spain [ 17 , 18 ], and Turkey [ 19 ]. Previous tests by our research group also confirmed that chestnut honey had the highest antibacterial effect, compared to a set of varietal honeys harvested in Hungary, including lavender, linden, acacia, sunflower, milkweed, and goldenrod honeys [ 20 ].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Among unifloral honeys, which are derived predominantly from a certain plant species or genus, the amber to dark brown, somewhat bitter-tasting chestnut honey proved to be superior in terms of antibacterial activity in comparison to other honey types from Portugal [ 16 ], Spain [ 17 , 18 ], and Turkey [ 19 ]. Previous tests by our research group also confirmed that chestnut honey had the highest antibacterial effect, compared to a set of varietal honeys harvested in Hungary, including lavender, linden, acacia, sunflower, milkweed, and goldenrod honeys [ 20 ].…”
Section: Introductionsupporting
confidence: 71%
“…In order to visualize our results, we took SEM images of P. aeruginosa -MRSA untreated samples, as well as samples treated with different honey solutions (in the case of the P. aeruginosa -MRSA and P. aeruginosa - S. epidermidis combinations: 6% honey solution, S. epidermidis -MRSA: 4% honey solution), based on the description of Balázs et al, 2023 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The high sugar content and viscosity of honey have been shown to play a crucial role in inhibiting microbial growth and preventing the formation of biofilms. Furthermore, the biofilm matrix is composed of polysaccharides, and recent studies have shown that sugar molecules are also utilized as chemical messengers between bacterial species within the biofilm structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…In one investigation, Solidago extract demonstrated the capability to decrease E. coli adhesion to plastic surfaces by as much as 80%. In a separate study, Solidago extract was observed to disrupt the extracellular matrix within S. aureus biofilms, resulting in the detachment of bacteria from the biofilm structure [26].…”
Section: Discussionmentioning
confidence: 96%